Obremenjenost zraka s cvetnim prahom - Kofol-Seliger, Andreja (Naše okolje, 2024)
The pollen measurement in September 2024 was performed in Izola, Ljubljana, Lendava, and Maribor. The hay fever season 2024 has ended with September, only in the Pannonian region there can still be a small amount of Ragweed pollen in the air in the first half of October, which will represent only a minimal health risk. In the autumn months Cedar trees are flowering, releasing large amounts of pollen, that can cover the surfaces near the trees and turn them yellow. In this time of the year the trees are preparing for winter rest - dormancy. Already in December, there can be a few Hazel, Alder and Cypress grains in the air, announcing the arrival of the new season. Spaeth's Alder, an ornamental species usually starts to bloom in December, its pollen can be responsible for Christmas hay fever. With September, we conclude our monthly pollen reports for this year, monitoring at all stations will continue in October, November and December. We will carry on with our monthly activity when the airborne pollen concentrations will rise again, presumably already in January 2025.
Keywords: alergeni; alergije; alergijske reakcije; cvetni prah